An evaluation of drug use in the municipal health care service of Campo Grande-MS (Revista Brasileira de Ciências Farmacêuticas, 2002)
The rational use of therapeutic drugs is arising as a consequence of an increase in the search for advanced therapeutic drugs. The therapeutic drugs use, that is a pharmacoepidemiology deal, can give evidence of how a society manage with all steps of therapeutic drugs use and also all consequence of this use. The therapeutic drugs use evaluation can demonstrate how healthyness/ilness link is handled in that society. The aim of this study was an evaluation of therapeutic drugs use at the Campo Grande/ MS public health. WHO indicators were used in this research. The evaluation was done using the medical prescrition indicator. The data were collected in 12 health care units between July 1998 and June 1999. One thousand four hundred eighty prescriptions were analyzed, 1456 medical visits and 1498 dispensations were followed and 735 patients were interviewed. The results were in agreement with other results in other country regions. However, important differences were found in antibiotics and injectable prescritions among different health care unit staffs evaluated. These differences sugested the necessity of more specific studies. The quality of the users attendance must be improved. The Local Essential Drugs List must be always available and also updated to health care unit staff.